Bright brown baby : a treasury - Pinkney, Andrea Davis (Orchard Books, an imprint of Scholastic Inc., 2021)
The New York Times best-selling and award-winning duo present this celebration of Black and Brown babies and the happiness, gentle moments and endless love shared between children and their caregivers.